2013
DOI: 10.1111/age.12010
|View full text |Cite
|
Sign up to set email alerts
|

Allelic heterogeneity ofFGF5mutations causes the long-hair phenotype in dogs

Abstract: Hitherto, the only known mutant gene leading to the long-hair phenotype in mammals is the fibroblast growth factor 5 (FGF5). In many dog breeds, the previously discovered FGF5:p.Cys95Phe mutation appeared completely concordant with the long-hair phenotype, but for some breeds, the long-hair phenotype could not be resolved. First, we studied the role of the FGF5:p.Cys95Phe and FGF5:g.145_150dupACCAGC mutations in 268 dogs descending from 27 breeds and seven wolves. As these mutations did not explain all the lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 11 publications
(36 reference statements)
2
39
0
2
Order By: Relevance
“…Hair growth was considered to be regulated by hairless gene, FOXI3 13, hypertrichosis gene, FGF13, Trps1, Sox9 1415, and hair overgrowth gene, ABCA5 16. However, natural long hair, well described angora phenotype, results from a regulator gene, FGF5 , in many kinds of mammals1718192021. Here FGF5 have been included in the candidate genes sets based on low heterozygosity and high genetic differentiation in IMCG population (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Hair growth was considered to be regulated by hairless gene, FOXI3 13, hypertrichosis gene, FGF13, Trps1, Sox9 1415, and hair overgrowth gene, ABCA5 16. However, natural long hair, well described angora phenotype, results from a regulator gene, FGF5 , in many kinds of mammals1718192021. Here FGF5 have been included in the candidate genes sets based on low heterozygosity and high genetic differentiation in IMCG population (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study on the sequence analysis of the FGF5 gene in short and long-haired corgis found that the FGF5:p.Cys95Phe mutation appeared to be completely concordant with the long-hair phenotype (Housley and Venta, 2006). Recent studies have indicated that all long-hair-associated mutations follow a recessive mode of inheritance, and allelic heterogeneity of FGF5 mutations causes the long-hair phenotype in dogs (Dierks et al, 2013). Similarly, mutations within the FGF5 gene are associated with hair length in cats (Drögemüller et al, 2007;Kehler et al, 2007).…”
Section: Introductionmentioning
confidence: 94%
“…Indeed, the angora mouse mutant carries a 2-kb loss-of-function deletion in Fgf5 and displays a delayed catagen onset and excessively long truncal hair [7]. Loss-of-function mutations associated with long-hair phenotypes have been described in several mammalian species including mice [4,8], dogs [9,10] and cats [11,12], which support a conserved role of FGF5 in the regulation of hair growth.…”
Section: Introductionmentioning
confidence: 99%